2018
DOI: 10.1128/aac.01959-17
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Antiheparanase Activity by PG545 Is Antiviral In Vitro and Protects against Ross River Virus Disease in Mice

Abstract: Recently we reported on the efficacy of pentosan polysulfate (PPS), a heparan sulfate mimetic, to reduce the recruitment of inflammatory infiltrates and protect the cartilage matrix from degradation in Ross River virus (RRV)-infected PPS-treated mice. Here, we describe both prophylactic and therapeutic treatment with PG545, a low-molecular-weight heparan sulfate mimetic, for arthritogenic alphaviral infection. We first assessed antiviral activity through a 50% plaque reduction assay. Increasing concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 44 publications
3
41
0
Order By: Relevance
“…In addition to direct antiviral activity shown against SARS-CoV-2, pixatimod also has immunomodulatory effects which may alleviate some of the immunopathologies associated with moderate-severe COVID-19 patients. It inhibits the pro-inflammatory enzyme heparanase (Dredge et al, 2011) and has been demonstrated to suppress IL-6 in inflammatory (pancreatitis) and viral (Ross River virus) animal models in a process thought to be driven by elevated levels of heparanase , Supramaniam et al, 2018. Moreover, it blocks the heparanase-dependent invasion of macrophages into tumours in mouse cancer models (Ostapoff et al, 2013;Boyango et al, 2014;Barash et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition to direct antiviral activity shown against SARS-CoV-2, pixatimod also has immunomodulatory effects which may alleviate some of the immunopathologies associated with moderate-severe COVID-19 patients. It inhibits the pro-inflammatory enzyme heparanase (Dredge et al, 2011) and has been demonstrated to suppress IL-6 in inflammatory (pancreatitis) and viral (Ross River virus) animal models in a process thought to be driven by elevated levels of heparanase , Supramaniam et al, 2018. Moreover, it blocks the heparanase-dependent invasion of macrophages into tumours in mouse cancer models (Ostapoff et al, 2013;Boyango et al, 2014;Barash et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The virucidal activity is due to disruption of the viral lipid envelope by the lipophilic steroid side chain of pixatimod (see Fig 1A), an attribute not associated with heparin or other HS mimetics (Said et al, 2016). In vivo efficacy has been confirmed in a prophylactic mouse HSV-2 genital infection model (Said et al, 2016), a prophylactic Ross River virus mouse model (Supramaniam et al, 2018) and a therapeutic Dengue virus mouse model (Modhiran et al, 2019).…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Pentosan polysulfate is used for the treatment of interstitial cystitis and osteoarthritis, whereas pixatimod is currently developed as an anticancer drug. Both drugs have been reported to reduce the severity of alphavirus-induced disease in vivo through the modulation of inflammatory infiltrates and cytokine levels [ 97 , 98 ]. Treatment of mice infected with RRV or CHIKV with pentosan polysulfate ( Figure 3 ) resulted in a significant disease amelioration and protection of cartilages [ 97 ].…”
Section: Antiviral Strategiesmentioning
confidence: 99%